Altered interhemispheric functional connectivity in patients with comitant exotropia before and after surgery: a resting-state fMRI study - Chen, Xiang-Xun; Chen, Wen; Hu, Hao; Zhao, Meng; Liu, Hu; Xu, Xiao-Quan; Wu, Fei-Yun; Wang, Jie (Frontiers in Human Neuroscience, 2023)
Purpose: To assess the interhemispheric homotopic connectivity alterations in patients with comitant exotropia (CE) before and after surgery, using resting-state functional magnetic resonance imaging (rs-fMRI) with voxel-mirrored homotopic connectivity (VMHC). Methods: Thirty-four patients with CE and twenty-four well-matched healthy controls (HCs) were enrolled to undergo a preoperative rs-fMRI scan. The rs-fMRI scan was performed again in twenty-four patients one month after surgery. The VMHC method was applied to evaluate the group differences of interhemispheric functional connectivity. The correlations between VMHC values and clinical variables were analyzed in the patient group. Results: Compared with HCs, 34 patients with CE showed significantly increased VMHC values in occipital lobe (cuneus/ superior occipital gyrus/ middle occipital gyrus/ calcarine), cerebellar area 8/ cerebellar Crus1 area, and cerebellar Crus1 area. In CE group, VMHC in the cuneus was positively correlated with stereoacuity (r = 0.417, P = 0.014), meanwhile VMHC in the cerebellar Crus1 area was positively correlated with stereoacuity (r = 0.395, P = 0.021). One month after surgery, the 24 CE patients with follow-up showed decreased VMHC values in the cuneus and superior occipital gyrus compared with preoperative collection, meanwhile, non-significant difference compared with HCs. Conclusion: Our study revealed the interhemispheric homotopic connectivity changes of patients with CE in the occipital lobe and cerebellum before and after surgery. The findings may provide a new perspective for the neurological alterations of CE.